2016
DOI: 10.1111/liv.13168
|View full text |Cite
|
Sign up to set email alerts
|

Survey of hepatitis B knowledge and stigma among chronically infected patients and uninfected persons in Beijing, China

Abstract: Despite high prevalence of CHB in China, our study shows knowledge is limited and there is significant societal and internalized stigma associated with HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
88
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 21 publications
11
88
2
Order By: Relevance
“…These misconceptions are well documented among Chinese‐speakers in China and the United States, as well as other East and Southeast Asian populations . On the other hand, shame and blame towards HBV carriers was relatively low, which is also similar to prior studies . Our findings demonstrate that HBV stigma among MSM in China is similar to HBV stigma in the general population.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These misconceptions are well documented among Chinese‐speakers in China and the United States, as well as other East and Southeast Asian populations . On the other hand, shame and blame towards HBV carriers was relatively low, which is also similar to prior studies . Our findings demonstrate that HBV stigma among MSM in China is similar to HBV stigma in the general population.…”
Section: Discussionsupporting
confidence: 88%
“…For our study, we operationalize HBV stigma as a social process involving discrimination at work or at school, devaluation in interpersonal relationships, fear of physical contact, or shame and blame towards persons with HBV. These four domains have been identified in the HBV stigma literature as key attributes and create a framework for assessing HBV stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection has been reported worldwide, with an estimated burden of 250 million cases, and has been associated with high mortality rates resulting from complications including cirrhosis and hepatocellular carcinoma (HCC) 1 . There are effective prevention and treatment strategies available, including vaccination and suppressive antiviral therapy, both of which also contribute to prevention of vertical transmission 2 . The Global Hepatitis Health Sector Strategy is aiming for the elimination of viral hepatitis as a public health threat by 2030 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Prevention requires HBV-infected mothers to be aware of their disease status and to understand the consequences of HBV transmission to their child. Although, many studies have demonstrated that insufficient knowledge of HBV infection in the general public [11, 12, 13, 14, 15, 16] and among health care workers [17, 18, 19] is associated with high prevalence of hepatitis B, only a few studies have assessed knowledge of hepatitis B and MTCT among pregnant women [20, 21, 22]. These studies also indicated similar gaps of knowledge; however, they did not assess the attitudes of the mothers towards methods of preventing MTCT of hepatitis B.…”
Section: Introductionmentioning
confidence: 99%